Study on Performance of Compliant Foil Gas Film Seal Based on Different Texture Bottom Designs - Zhenpeng He; Yuchen Zou; Jiaxin Si; Ziyi Lei; Ning Li; Yuhang Guo (Lubricants)
To investigate how texture affects the sealing performance of compliant foil, a systematic analysis was conducted on the impact of various bottom shapes of rectangular textures on the gas film sealing performance of the foil. The Reynolds equation for the compliant foil seal is solved using the finite difference method., and the average gas film pressure, bearing capacity, leakage, and friction performance parameters of the compliant foil gas film seal are obtained. The results indicate that the convergent right triangle bottom shape texture provides the best sealing performance, with the average gas film pressure reaching 1.457. This is 0.10% higher than the non-textured case and 0.55% higher than the horizontal bottom shape texture. For the same texture area ratio, increasing the texture length in the axial direction improves the dynamic pressure effect. When the aspect ratio is 2/1, the gas film pressure reaches its maximum, and leakage is minimized. With an area ratio of 0.25 and a depth of 5 μm, the compliant foil gas film seal achieves the highest pressure and the lowest leakage. Compared with the average pressure without texture, the average pressure can be increased by 0.83%, and the leakage can be reduced by 6.61%.